PREVALENCE OF PARTIAL EDENTULISM OF KENNEDY’S CLASS I CLASSIFICATION BASED ON DIFFERENT AGE GROUPS AND ARCH - A RETROSPECTIVE STUDY - Srinisha Marimuthu,; Kiran Kumar Pandurangan,; Hemavathy Muralidoss, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Partial edentulism indicates missing one or two teeth in the dental arches.The goal of partial edentulous arches classification provides communication between students, dental practitioners, technicians for planning a treatment and help to design the partial denture.Classification will also predict the removable partial denture design.Hence, the aim of the present study was to evaluate the prevalence of partial edentulousness (Kennedy’s Class I) among different age groups and arch. An institution based retrospective study was conducted among dental patients who visited Private Dental Hospital between 1st June 2019 and 30th Nov 2019.We reviewed patient records and analysed the data of 86000 patients at the private dental hospital. The study was done in 103 patients based on age groups and arch by doing oral examination for determining the prevalence of partial edentulism of Kennedy’s Class I. Collected data was tabulated in excel sheet and imported in SPSS version 20 for statistical analysis.Among 103 patients, 51 to 60 years age group patients showed a higher prevalence of Kennedy's Class I (37.9%). Mandibular arch(51.5%) showed higher prevalence than maxillary arch(48.5%).